O sistema de comunicação organizacional na governança dos conflitos com a administração pública - Smolenaars, Claudine Costa (Universidade do Vale do Rio dos Sinos, 2022)
The object of this research is the organizational communication of the National Institute of Social Security with the other actors of public social security policy. The research problem is the limited communication scenario, which does not enable a systemic view for effective action and for better coordination in the resolution of problems and conflicts, complex and structural, related to the judicialization of social security. The question then is how to promote communicational alignment between the INSS and the other organizations, to achieve network cooperation and mitigate conflicts and judicialization? As a hypothesis, the structuring of an organizational communication system, based on the understanding of the structure and functioning of the Interinstitutional Social Security Forum, established within the scope of TRF4, will enable the coordination and standardization of the flows of the management processes of the interests and demands of the organizations, as an efficient method for network collaboration and conflict governance. As a general objective, the research intends to promote the institutional reinforcement of systematized communication to achieve the Open State. As specific objectives, the structure and functioning of INSS organizational communication will be analysed, in the light of systems theory; demonstrate how the communication problem between the INSS and the impacted public organizations aggravates the phenomenon of the judicialization of social security; will present the structure and functioning of the communication system, based on the systematization of the Interinstitutional Social Security Forum of TRF4, bringing public governance as a premise for participation in the system; and, finally, as a practical and applicable delivery, it will build the artifact “Guide to Implement the Communication Forum”. The relevance of the research is due to the impact of judicialization on the development of the country, since in addition to affecting the efficiency in the protection of important legal assets, it also affects the sustainability of public organizations. The methodology of the present research was divided into two: one for the investigation, the other for the elaboration of the product, object of the requirement of the Professional Master's Degree. To confirm the hypothesis, the theoretical framework used Niklas Luhmann's systems theory; a qualitative research method was used, with inductive reasoning. As a research technique, a systematic review of the literature was carried out, exploratory data collection and document analysis, based on already recognized data research, as well as from public documents available on the organizations' websites. For the artifact, the Design Science Research (DSR) methodology was used. The findings reveal that the Interinstitutional Social Security Forum of the Federal Regional Court of the 4th Region has been showing consistent results, in its more than ten years of existence and operation. The conclusion reveals the confirmation of the hypothesis, that an organizational communication system, such as the Forum, provides an environment of collaboration and cooperation to mitigate the problem of judicialization.
Keywords: Conflito; Judicialização; Comunicação sistêmica; Governança pública; Estado aberto; Conflict; Judicialization; Systemic communication; Public governance; Open state; ACCNPQ::Ciências Sociais Aplicadas::Direito